Effectiveness Bale Educational Merariq Kodeq (Bedeq) Assistance to Pre-Pregnancy Readiness In Early Married Couples as an Effort to Prevent Stunting - Ekayani, Ni Putu Karunia; Anggraeni, Ni Putu Dian Ayu; Setyorini, Dhiana; Sopiatun, Rita (Jurnal Kesehatan Prima, 2024)
Pregnancy due to merariq kodeq or getting married at an early age can be risky because, at that age, teenagers are relatively unable to accept physical and psychological changes. Efforts that can be made for couples who marry at an early age to prepare for a healthy pregnancy are through mentoring. The aim of this research is to analyze the effectiveness of Merariq Kodeq (Bedeq) Education Bale Assistance on Pre-Pregnancy Readiness. This type of research is Quasi-Experimental research with a Post-Test only with Control Group Design approach with a total sampling technique of 60 people divided into two groups, namely the BEDEQ assistance intervention group and the Catin service counseling control group with 30 people in each group. The results of the study showed that there was a significant difference between the intervention group and the control group, with a p value of 0.008 (p value 0.05). Most of the respondents had good knowledge after receiving the Bedeq intervention assistance treatment for prospective brides and grooms, 18 respondents (81.8%) and married couples, 7 people (87.5%). Meanwhile, in the control group, the level of knowledge about healthy pre-pregnancy among prospective brides and grooms was 10 people (45.5%) had good knowledge, 9 people (40.9%) had sufficient knowledge, and 3 people (13.6%) had poor knowledge. With BEDEQ assistance, the community, especially teenage brides and grooms, can pay more attention to their physical and psychological conditions in preparing for a healthy pre-pregnancy to prevent the risk of stunting